Viral agents associated with acute diarrhea among outpatient children in southeastern China - Chen, Yu; Li, Zhongjie; Han, Dongsheng; Cui, Dawei; Chen, Xiao; Zheng, Shufa; Yu, Fei; Liu, Jia; Lai, Shengjie; Yan, Yansheng; Lin, Zhong; Shi, Zhiyang; et al. (The Pediatric infectious disease journal, 2013)
Acute diarrhea is a leading cause of childhood morbidity and mortality worldwide, but there have been few reports on the causative viruses associated with acute diarrhea among outpatient children in developing countries. This study was conducted to identify the viral agents in outpatient children with acute diarrhea in southeastern China. Eight hundred eleven outpatient children 5 years or younger with acute diarrhea were enrolled. Five enteric viruses were determined by enzyme-linked immunosorbent assay and multiplex reverse transcription-polymerase chain reaction for each stool specimen. At least 1 virus was detected in 353 (43.5%) of the subjects. The proportions of rotavirus, norovirus, sapovirus, adenovirus and astrovirus were 25.5%, 18.1%, 4.4%, 2.7% and 1.2%, respectively. G3P[8] was the most prevalent rotavirus strain. Mixed infections were observed in 65 cases, among which the most prevalent coinfection was rotavirus with other viruses (58 cases, 89.2%). Rotavirus and norovirus infections showed marked and opposing seasonal patterns. Mixed infection was significantly more common in children older than 1 year (12.2%) than in those younger than 1 year (7.1%) (P = 0.026). Clinically, rotavirus infection presented with a longer duration (4.3 ± 6.7 days) and higher frequency (5.9 ± 2.0 times/d) of diarrhea than any other viral infection. Vomiting was more common for mixed infections than for single infections (P = 0.010). All the 5 common etiologies were detected in this study, with rotavirus and norovirus being the 2 leading agents. Mixed viral infections were common in outpatient children with acute diarrhea, and rotavirus seemed to play a major role in mixed infections.